Head and Maxillofacial Injuries in Child and Adolescent Victims of Automotive Accidents - Alessandro Leite Cavalcanti; Thiago Henrique de Araujo Lino; Thaliny Batista Sarmento de Oliveira; Thaisy Sarmento Batista de Oliveira; Andreia Medeiros Rodrigues Cardoso; Rodrigo Feliciano de Macedo; Wilton Wilney Nascimento Padilha; Alidianne Fabia Cabral Xavier (The Scientific World Journal)
Background. Victims of motor vehicle accidents may suffer multiple lesions, including maxillofacial injuries. The aim of this study was to evaluate the prevalence and factors associated with head, facial, and maxillofacial injuries in child and adolescent victims of automobile accidents. A cross-sectional study was carried out with analysis of forensic medical reports from the Legal Medical Institute of Campina Grande, Brazil, between January 2008 and December 2011. Descriptive and inferential statistical analysis was conducted using the chi-square test (α = 0.05). From 1613 medical reports analyzed, the sample is composed 232 (14.4%) reports referring to child and adolescent victims of automobile accidents aged 0–19 years of both sexes. Victims were mostly adolescents aged from 15 to 19 years (64.2%), males (73.7%), and motorcyclists (51.3%). More than half of the victims had single lesions (54.3%) located in the head (20.7%) and face (21.6%). Head injuries occurred more frequently in children aged 0–4 years (53.8%, PR = 5.065, 95% CI = 1.617–5.870) and pedestrians (30.4%, PR = 2.039, 95% CI = 1.024–4.061), while facial and maxillofacial injuries occurred in higher proportion among females (31.1%, PR = 0.489, 95% CI = 0.251–0.954). Our findings suggest that accidents involving motorcyclists are the most prevalent, affecting male adolescents aged from 15 to 19 years, resulting in a high frequency of injuries in the head and face regions.